The HEV Ventilator: at the interface between particle physics and biomedical engineering. Issue 3 (16th March 2022) - Buytaert, Jan; Collins, Paula; Abed Abud, Adam; Allport, Phil; Pazos Álvarez, Antonio; Akiba, Kazuyoshi; de Aguiar Francisco, Oscar Augusto; Bay, Aurelio; Bernard, Florian; Baron, Sophie; Bertella, Claudia; Brunner, Josef X.; et al.
Abstract : A high-quality, low-cost ventilator, dubbed HEV, has been developed by the particle physics community working together with biomedical engineers and physicians around the world. The HEV design is suitable for use both in and out of hospital intensive care units, provides a variety of modes and is capable of supporting spontaneous breathing and supplying oxygen-enriched air. An external air supply can be combined with the unit for use in situations where compressed air is not readily available. HEV supports remote training and post market surveillance via a Web interface and data logging to complement standard touch screen operation, making it suitable for a wide range of geographical deployment. The HEV design places emphasis on the ventilation performance, especially the quality and accuracy of the pressure curves, reactivity of the trigger, measurement of delivered volume and control of oxygen mixing, delivering a global performance which will be applicable to ventilator needs beyond the COVID-19 pandemic. This article describes the conceptual design and presents the prototype units together with a performance evaluation.